PENDEKATAN PENDIDIKAN SPIRITUAL UNTUK MENANGGULANGI KENAKALAN REMAJA (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2020)
Adolescence is a period of transition. At that time, there was a process leading to intellectual, spiritual and physical maturation in order to form a clear identity when facing doubts who their realities, resulting in emotional turmoil and mental stress. So to know the prevention of promiscuity in adolescence needs to be studied approaches to the development of their spiritual intelligence. The results of the study show that ways to deal with promiscuity are pursued by providing assistance to adolescents to formulate their life goals, short-term, medium-term life goals to long-term life goals, tell exemplary stories, interesting and memorable stories, such as the stories of the prophets, or another hero, discussing issues with a spiritual perspective, involving youth in religious rituals, bringing youth to people who suffer, and visiting the procession of death will make teens sensitive to each other so as to encourage youth to do good for others, teach the Qur'an and explain their meaning in their life.